Umbilical artery systolic to diastolic ratio is associated with growth and myocardial performance in infants with hypoplastic left heart syndrome. (28th November 2013) - Miller, Thomas A.; Joss‐Moore, Lisa; Menon, Shaji C.; Weng, Cindy; Puchalski, Michael D.
ABSTRACT Objective Despite standardization in care, heterogeneity in outcomes persists for infants with hypoplastic left heart syndrome (HLHS). One potential factor is in utero stressors. Uteroplacental insufficiency (UPI) induces systemic vascular and myocardial adaptations in the absence of structural heart disease. The effect of UPI in HLHS is unknown. Methods We retrospectively analyzed infants undergoing Norwood palliation for HLHS from 2007 to 2012. We compared the umbilical artery systolic to diastolic (SD) ratio to growth outcomes and postoperative right ventricular function. Results Forty three infants met our inclusion criteria. Fetuses without a declining SD ratio with advancing gestational age had asymmetric birth biometry, defined as birth weight minus head circumference z scores (−0.9 vs −0.05, p < 0.01). The SD ratio near the end of gestation negatively correlated with asymmetric birth biometry (R = −0.521, p < 0.01) and interstage growth (R = −0.49, p = 0.04). Males with higher SD ratios had a greater postoperative incidence of abnormal right ventricular function. Conclusions A higher umbilical artery SD ratio was associated with asymmetric prenatal growth, poor weight gain, and decreased myocardial performance in infants with HLHS. Better understanding of UPI's effects on cardiovascular development and metabolism in HLHS will help identify new strategies for targeting morbidity in this high risk population. © 2013 John Wiley & Sons, Ltd.